PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI YANG DIMESIASI OLEH KEPUASAN KERJA - Jumaisa Jumaisa; Nurwati Nurwati; Muhammad Masri (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study was to analyze and explain the role of competencies on job satisfaction and employee performance and organizational commitment to job satisfaction and employee performance and job satisfaction on employee performance, then the mediating role of job satisfaction between competency and organizational commitment to employee performance at the Wakatobi District Transportation Agency. The research analysis unit is an employee of the Department of Transportation of Wakatobi Regency. The sample respondents were 50 employees. Data collection techniques were carried out by distributing questionnaires followed by conducting in-depth interviews. The analytical method used in testing the hypothesis is Partial Least Square (PLS). Qualitative information is used to explore additional information relating to the results of hypothesis testing.The results of this study indicate that: there is a significant influence between competency and organizational commitment to job satisfaction on employee performance, as well as competency on employee performance, this illustrates that high organizational competency and commitment will have an impact on job satisfaction, the implications of which is improving performance . However, organizational commitment is not significant to employee performance, this indicates that a high commitment of an employee to the organization cannot influence the results of employee performance, meaning that work is not only based on commitment but there are other things that must be emphasized including skill abilities and even employee satisfaction. The workload given to him. Then there is a significant relationship between competency and organizational commitment to employee performance mediated by job satisfaction, meaning that organizational competence and commitment can significantly improve employee performance triggered by increased employee job satisfaction. Keywords: competence, organizational commitment, job satisfaction, employee performance